2013
DOI: 10.1164/rccm.201209-1722oc
|View full text |Cite
|
Sign up to set email alerts
|

Mortality by Level of Emphysema and Airway Wall Thickness

Abstract: AWT affected mortality with increasing degree of emphysema, whereas CT measure of emphysema was a strong independent mortality predictor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
170
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(180 citation statements)
references
References 32 publications
7
170
1
2
Order By: Relevance
“…Subsequent studies 54,55 , with smaller cohorts but longer follow-up time (4 versus 8 years) and with different AL severity observed a significant association of lung attenuation areas low attenuation area (% LAA) and the prognosis of the disease 54,55 . Patient selection and emphysema evaluation criteria (% LAA) make comparisons between studies difficult.…”
Section: Emphysema and Mortalitymentioning
confidence: 97%
See 1 more Smart Citation
“…Subsequent studies 54,55 , with smaller cohorts but longer follow-up time (4 versus 8 years) and with different AL severity observed a significant association of lung attenuation areas low attenuation area (% LAA) and the prognosis of the disease 54,55 . Patient selection and emphysema evaluation criteria (% LAA) make comparisons between studies difficult.…”
Section: Emphysema and Mortalitymentioning
confidence: 97%
“…Johannessen et al 55 , have shown that the degree of emphysema predicts all-cause, respiratory and cardiovascular mortality in a population-based sample of subjects with and without COPD. Patients with a degree of emphysema…”
Section: Emphysema and Mortalitymentioning
confidence: 99%
“…In patients with α1-antitrypsin deficiency, density-based emphysema measurement has shown a superior accuracy in detecting worsening of emphysema, and therefore has been accepted as the effective diagnostic method for detecting disease progression (16). The CT density mask method was found to have an association with COPD mortality, and is reported to be a stronger predictive parameter for cardiac and respiratory mortality than global initiative for chronic obstructive lung disease (GOLD) staging (17,18). Patients with greater quantitative measures of emphysema were reported to have more rapid decline of PFT parameters (19).…”
Section: Emphysema Quantificationmentioning
confidence: 99%
“…Recently, it was reported that the level of emphysema predicts all-cause mortality as well as respiratory and cardiovascular mortality in a population-based sample of subjects with and without COPD. Airway wall thickness is associated with respiratory mortality in those with severe emphysema [47]. This is a new point to measure the mortality risk and is substantially important for COPD assessment.…”
Section: ) Imagingmentioning
confidence: 99%
“…This phenotype usually has a lower BMI. The degree of dyspnea, intolerance to exercise, and hyperinflation are predictors of mortality [47].…”
Section: ) Phenotypes and Biomarkersmentioning
confidence: 99%